Ecological Awareness and Behavior in the Context of Selected Research - Joanna GORNIAK; Jakub DONSKI-LESIUK (Communications of International Proceedings, 2021)
The article is a review of selected studies devoted to ecological awareness and pro-ecological behavior. It deals with the topic of the economic dimension of specific attitudes, consistent with the current direction of thinking about the role of man in the field of environmental protection. It reflects the conclusions of the literature review preceding the development of own empirical research concepts. Research demonstrating the relationship between how a person (consumer) thinks and what purchasing decisions they choose. Since it is known that the social attitude is important when making decisions, and that man in the modern world is also a consumer, the article points to the existence of a specific research gap. It concerns the organization of logistic processes, taking into account the client's willingness to participate in the promotion of the desired ecological attitudes, which is of interest to management and quality. While the authors focus on the research achievements related to Poland to date, they do so against the background of previous foreign achievements.
Keywords: Consumer Behavior; Consumer Attitudes; Individual Decision; Sustainable Development